Validitas dan reliabilitas kuesioner literasi gizi pada remaja (Nulit) di Wilayah Pascabencana - Nikmah Utami Dewi; Ali Khomsan; Cesilia Meti Dwiriani; Hadi Riyadi; Ikeu Ekayanti (AcTion: Aceh Nutrition Journal, 2023)
The validation of the nutritional literacy questionnaire with a broader concept has never been published in Indonesia. This study aims to describe the validation of a nutritional literacy questionnaire (Nulit) in adolescents in post-disaster areas. Content validation was carried out qualitatively and quantitatively. They involve nine panellists by calculating the content validity index (CVI) and multi-rater kappa statistics. Face validation involved ten adolescents living with their mothers in Palu during the 2018 natural disaster. The face validation, item validity, and reliability were assessed by the impact score, the correlation score of each item with the total score, and the value of Cronbach's Coefficient Alpha. The results found that the I-CVI on all items was between 0,78 - 1, which is considered very good. The validation of the questionnaire display found the statement items to be essential and appropriate in the daily life of adolescents, and the impact factor value was 3,9 - 4,3. A total of 21 items are valid; the Cronbach's alpha value is FNL= 0,73, INL= 0,70 and CNL= 0,71. In conclusion, the Nulit Questionnaire is valid and reliable for measuring nutritional literacy in adolescents in post-disaster areas.